Case marking is different in monolingual and heritage Bosnian in digitally elicited oral texts - Jažić, Ilma; Gagarina, Natalia; Perovic, Alexandra (Frontiers in Psychology, 2023)
Heritage languages may differ from baseline languages spoken in the home country, particularly in the domains of vocabulary, morphosyntax and phonology. The success of acquiring and maintaining a heritage language may depend on a range of factors, from the age of acquisition of the second language; quantity and quality of input and frequency of first language use, to non-linguistic factors, such as Socio-Economic Status (SES). To investigate case marking accuracy in heritage Bosnian in relation to these very factors, we recruited 20 heritage Bosnian speakers in Austria and Germany, and 20 monolingual Bosnian speakers in Bosnia, aged between 18-30 years. Participants were assessed remotely in two sessions, on a battery of tests that included a background language questionnaire investigating participants’ history of language acquisition, current usage and SES, and a newly adapted Bosnian version of the Multilingual Assessment Instrument for Narratives (MAIN). A significant difference in case marking accuracy was found between the two groups, despite the 97% correct performance in the heritage speakers, and an almost 100% performance of the monolinguals. In the heritage speakers group only, errors indicated a trend towards case system simplification as well as uncertainty in distinguishing between case meanings. The use of Bosnian, assessed through quantity and quality of input, as well as frequency of current usage, was shown to be a significant predictor of case marking accuracy in heritage speakers. In contrast, SES and age of acquisition of German did not play a role in these participants’ case accuracy. The observed patterns of quantitative and qualitative differences in the case marking accuracy between heritage Bosnian speakers and their monolingual counterparts, in the face of a high level of accuracy, contribute to our understanding of the heritage language attainment in more diverse language dyads where L1 is a lesser studied language.